The syntax of depictives: subjects, modes of judgement and I-L/S-L properties - Ardid-Gumiel, Ana (ZAS Papers in Linguistics, 2001)
In this work, I provide an analysis of adjectival depictive constructions which accounts for most of their fundamental properties. First, I focus on the restrictions having to do with the integration of the depictive and the verbal predicate: they are based on aspectual compatibility between the two predicates, which, in turn, will depend on the ability, on the part of the depictive, to make reference to some (sub)event in the event structure of the verbal predicate. Facts not captured by previous approaches in the literature will be straightforwardly accounted for, among them the possibility to have I-L depictive constructions, and the impossibility to combine a depictive with some non-stative verbal predicates. Second, it will be shown that the informational import of the depictive in the sentence can be equivalent to that of the verbal predicate: both can be the primary lexical basis of predication. This is reflected in the sentence in various ways, having to do with aspectual modifiers, and in the properties of the sentential subject. In this connection, we will reconsider the notion of subject, arguing that no subject-predicate relation takes place in the lexical domain of sentences, and hence that the argument the depictive is oriented to, the common argument, cannot be a subject of the depictive. Finally, a minimalist analysis is proposed for the syntax of the construction, in terms of direct syntactic merge of predicative constituents and sidewards (q-to-q) movement for the common argument, from the lexical domain of the depictive to the lexical domain of the verb. As to morphosyntactic properties, a syntactic Double Agree relation is assumed to hold between T/v, as probes, on the one hand, and the common argument and depictive, as simultaneous goals, on the other, which would allow for the deletion of Case features on both goals. The assumed presence of Structural Case on the adjectival depictive will be responsible for the well-known restriction on the orientation of depictives to the sentential subject or object.